Travel and the risk of symptomatic venous thromboembolism - ten Wolde, Marije; Kraaijenhagen, Roderik A.; Schiereck, Jan; Hagen, Petronella J.; Mathijssen, Joost J.; Mac Gillavry, Melvin R.; Koopman, Maria M.W; Büller, Harry R. (Thrombosis and Haemostasis, 2003)
Whether long-distance travel and symptomatic venous thromboembolism (VTE) are associated is debated. On the basis of the available literature a fair risk estimate cannot be obtained. We estimated an accurate odds ratio for the relationship between recent travelling and symptomatic VTE.From three case-control studies consisting of 788 and 170 patients with clinically suspected deep vein thrombosis (DVT) and 989 patients with clinically suspected pulmonary embolism (PE) referred for diagnostic work-up, a pooled odds ratio for the relation between travel and symptomatic VTE was calculated. Cases were patients in whom the diagnosis was confirmed according to a diagnostic management strategy, whereas controls were patients in whom the diagnosis was excluded and who had an uneventful clinical follow-up. Patients were seen in the period April 1997 to September 2000. Travel history was recorded prior to diagnostic work-up.The pooled odds ratio for the association between any travel and symptomatic venous thromboembolism was 0.9 (95% CI: 0.6-1.4). The median travel time was 7 h (quartile range 4 to 10 h). Separate analyses performed for different types of transport (plane, car, bus or train) yielded comparable odds ratios. The analysis for duration of travelling showed an increased odds ratio of 2.5 (95% CI: 1.0-6.2) in the category of 10-15 h of travelling.This study shows that the average traveller does not have an increased risk for symptomatic venous thromboembolism. Only very long travelling (more than 10 h) may be associated with venous thromboembolic disease.
Keywords: Deep vein thrombosis; pulmonary embolism; travel